Geographic accessibility of healthcare services and health seeking behaviours of rural communities in Kudat and Pitas areas of Sabah - Naing Oo Tha; Wendy Diana Shoesmith; Tan, Bih Yuan; Mohd Yusof Ibrahim; Syed Shajee Hussein (2020)
Introduction: One of the aims outlined in Malaysia’s Health Vision 2020 is to be a nation of healthy individuals, families, and communities through an equitable, affordable, efficient, environmentally adaptable, and consumer friendly healthcare system. Sabah faces tremendous challenges to provide the best care for patients. For example, Sabah's unique geographical location and landscape, such as steep hills and rivers, is one of the challenges that health staff faces. Objectives of this study aimed to examine the prevalence of geographical accessibility, types of healthcare services, and the types of health seeking behaviour in 2 northern rural areas of Sabah to assess the geographic accessibility and availability of healthcare services. Materials and Methods: A community-based cross-sectional study was conducted in two rural areas in Sabah—Kudat and Pitas. Data collection was done by using questionnaire and face–to-face interviews. Results: It was found that 48% of the study population sought healthcare and they mainly chose healthcare services from hospitals and health clinics. Conclusion: Half of the population in the areas studied used healthcare in the last year. The choice of using a public hospital or community health clinics was determined by distance from residence.